The relevance of evidence as the main criterion for evaluating evidence (Journal of actual problems of jurisprudence, 2018)
Under the relevant evidence should be understood in the case of the use of evidence relevant to the case. Range of evidence that can convince the investigator and the court of the existence of certain circumstances, the law is not limited. This is – any factual data that meet a series of requirements, and above all they must be able to confirm or deny the interest of the investigator and the court the circumstances of the case. In this article, the authors reveal the concept and content of the relevance of evidence, as well as some of the problems the relevance of evidence in criminal proceedings. Key words: evidence, relevance of evidence, circumstantial evidence, evaluation of the evidence, persons involved in criminal proceedings.